Prevalence of periapical lesions in endodontically treated teeth at the FOP-UPE specialization clinic - Travassos, Rosana Maria Coelho; Júnior, Paulo Maurício Reis de Melo; de Menezes, Sílvio Emanuel Acioly Conrado; de Santana, Kassia Regina; dos Santos, Pedro Guimarães Sampio Trajano; Ataíde, Juliana Perez Leyva; Cunha, Rodolfo Scavuzzi Carneiro; Filho, Ailton Coelho de Ataíde; Filho, Eudoro de Queiroz Marques; Júnior, José Neilton de Araujo; Rocha, Vitória Souza (Seven Editora, 2024)
The aim of the present study is to determine the prevalence of periradicular lesions in permanent anterior teeth treated endodontically and in teeth with intraradicular retainers through the analysis of periapical radiographs. A survey of 1000 radiographs of patients treated endodontically in the dental clinics of the Faculty of Dentistry of Pernambuco – FOP/UPE was carried out, constituting a sample of 467 radiographs that fit the established criteria. In the analysis, the following data were collected: canal obturation limit, presence or absence of periapical lesion, homogeneity of the filling material characterized as without failure or with failure when presence of any radiotransparency in the root canal, presence or absence of the space between the intraradicular retainer and filling material and coronary sealing classified as adequate or inadequate. Through the data obtained, the highest frequencies corresponded to maxillary incisor teeth. It indicated that the filling limit characterized as beyond the apical foramen was the one with the highest rate of periapical lesion presence (66.7%), followed by the filling limit characterized as exact (32.4%). DOI:https://doi.org/10.56238/sevened2024.026-043